Sunk Costs and Antitrust Barriers to Entry - Schmalensee, Richard (American Economic Review, 2004)
US antitrust policy takes as its objective consumer welfare, not total economic welfare. With that objective, Joe Bain's definition of entry barriers is more useful than George Stigler's or definitions based on economic welfare. It follows that economies of scale that involve sunk costs may create antitrust barriers to entry. A simple model shows that sunk costs without scale economies may discourage entry without creating an antitrust entry barrier.(This abstract was borrowed from another version of this item.)